Effects of High Temperature and Different Salt Solutions on Basalt Fiber-Reinforced Composites’ Bonded Joint Durability Impact - Peng, Han; Lin, Yinghao; Chen, Zeshao; Ma, Shengtao; Shangguan, Linjian; Cheng, Ruixue; Fan, Yisa (Coatings (Basel), 2023)
Fiber-reinforced composites are widely used in industrial development due to their excellent performance, and the study of basalt fiber-reinforced resin (BFRP) as a new type of economical and environmentally friendly material is highly valued, since harsh environments can affect the durability of bonded joints. In this paper, the Araldite® 2015 adhesive for BFRP–BFRP single lap joints (SLJs) was selected as the subject of study and the joints were analyzed in aging experiments in three environments: deionized water (DW), 3.5% NaCl solution, and 5% NaCl solution at 80 °C for 0 days (no aging), 10 days, 20 days, and 30 days. Using Fick’s second law to describe water absorption in joints and materials, the comparison shows that the water absorption in the joints occurs primarily in the adhesive. Differential scanning calorimetry (DSC) was used to characterize the decrease in the glass transition temperature (Tg) of the adhesive at each failure point, and the thermogravimetric analysis (TGA) tests showed that moisture and heat led to the degradation of the polymer material in the joint. The failure strength of the joints in quasi-static tensile tests was positively correlated with the moisture content of the solution, and the changes in the absorption peaks of the functional groups of the adhesive after aging were observed. The comprehensive macro-micro failed section analysis showed that the water molecules damage the chemical properties of the adhesive, meaning that the adhesive and BFRP binding ability is decreased. The proportion of failure section tear decreased with the extension of the aging time, and a high temperature induced water evaporation and an adhesive post-curing reaction. The change in the failure mode is a result of the combined effect of the post-curing effect and hydrolysis reaction, which is validated by the results of the Fourier infrared spectroscopy (FTIR). This study contributes to an in-depth understanding of the effect of moisture and heat on the residual properties of bonded joints.